2002
DOI: 10.1021/ol025755k
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective O-Substitution of p-tert-Butylcalix[7]arene

Abstract: [structure: see text]. The first examples of selectively functionalized calix[7]arenes have been obtained by weak-base promoted O-alkylation or O-benzoylation of p-tert-butylcalix[7]arene. Mono-, 1,3- and 1,4-disubstituted calix[7]arenes have been obtained in workable yields, while the 1,2,4,6-tetrasubstitution was achieved with surprisingly high selectivity (50-88% yield) by using K2CO3 as base. A rationale for this finding is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[10] Interestingly, with respect to the original 28-membered ring of parent 1, the trimeric 3/4-cone-like sub-ring of 2 is scaled down to a 24-membered ring. In similar previous work, [20] it was shown that the conformational rigidification of a 23-membered sub-ring of a 1,5-tetramethylene-bridged calix [8]arene derivative was possible by curtailing the oxygen-through-the-annulus route when sufficiently bulky groups were appended at the lower rim of the calix [8]arene macrocycle.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…[10] Interestingly, with respect to the original 28-membered ring of parent 1, the trimeric 3/4-cone-like sub-ring of 2 is scaled down to a 24-membered ring. In similar previous work, [20] it was shown that the conformational rigidification of a 23-membered sub-ring of a 1,5-tetramethylene-bridged calix [8]arene derivative was possible by curtailing the oxygen-through-the-annulus route when sufficiently bulky groups were appended at the lower rim of the calix [8]arene macrocycle.…”
Section: Resultsmentioning
confidence: 93%
“…The first, obvious criterion followed to select compatible conformers was to discard those arrangements that lacked [8]. [23] closure of the calix [7]arene macrocycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first example of selectively functionalized calix[7]arenes has been obtained by weak-base promoted O-alkylation or O-benzoylation of p -tert-butylcalix[7]arene. Mono, 1,3- and 1,4-disubstituted calix[7]arenes have been obtained in workable yields, while the 1,2,4,6-tetra substitution was achieved with surprisingly high selectivity by 50–88% yield by using pottassium carbonate as the base [40] (Figure 13). …”
Section: Structural Modificationsmentioning
confidence: 99%